ANALISIS FAKTOR YANG MEMPENGARUHI PERUBAHAN STRUKTUR MODAL PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI PERIODE 2020-2022 (STIE Wijaya Mulya, 2025)
Analysis of Factors Influencing Changes in Capital Structure in Infrastructure Sector Companies Listed on the IDX for the 2020-2022 Period. Thesis. Accounting Department. Wijaya Mulya Surakarta College of Economics. Advisors: Dr. Sri Isfantin Puji Lestari, SE, MM and Dra. Endang Winarsih, SE, M.Sc.This research is a type of quantitative descriptive research. The subjects of this research are Infrastructure Companies listed on the Indonesia Stock Exchange. The formulation of this problem is How are the Influencing Factors, Asset Growth, Company Size, Growth Opportunity on the capital structure listed on the IDX?The aim is to test whether there is an influence of asset growth, company size, growth opportunity on the capital structure listed on the IDX. The number of samples taken is 46 Infrastructure companies listed on the Indonesia Stock Exchange in 2020-2022. The research method used is the non-probability sampling method, especially purposive sampling. The analysis techniques used are descriptive statistics, classical assumption tests, multiple regression analysis using the SPSS 25 program.The results of the study show the calculation of the t-test (partial) that asset growth has a significance of 0.000 ≤ 0.05, company size has a significance value of 0.000 ≤ 0.05 and growth opportunity has a significance value of 0.114 ≥ 0.05. while the calculation results show the F test (simultaneous) that there is a significance value of 0.000 ≤ 0.05.Based on the results of these tests, it can be concluded that asset growth partially has an influence on capital structure, company size partially has an influence on capital structure, and growth opportunity partially has no influence on capital structure. While simultaneously between the independent variables, namely asset growth, company size, growth opportunity have an influence on capital structure as a dependent variable. Asset growth and company size have a dominant influence on capital structure. Keywords : Asset Growth(X1), Company Size(X2), Growth Opportunity(X3), Capital Structure(Y)